2014
DOI: 10.1364/ao.53.003581
|View full text |Cite
|
Sign up to set email alerts
|

Photonic crystal fiber based dual-wavelength Q-switched fiber laser using graphene oxide as a saturable absorber

Abstract: A Q-switched dual-wavelength fiber laser with narrow channel spacing is proposed and demonstrated. The fiber laser is built around a 3 m long erbium doped fiber as the gain medium and a 10 cm long photonic crystal fiber (PCF) as the element used to generate the dual-wavelength output. The PCF has a solid core approximately 4.37 μm in diameter and is surrounded by microscopic air-holes with a diameter of about 5.06 μm each as well as a zero-dispersion wavelength of about 980 nm. A graphene oxide based saturable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The efficiency of the EDFL is calculated to be 1.1% from the slope of the output-power dependence. It is worthwhile that the efficiency of the dual-wavelength Q-switched laser based on the cavity suggested by us is somewhat higher than the values achieved with the other generation methods [2,16] and close to those reported in Refs. [1,4].…”
Section: Resultssupporting
confidence: 86%
“…The efficiency of the EDFL is calculated to be 1.1% from the slope of the output-power dependence. It is worthwhile that the efficiency of the dual-wavelength Q-switched laser based on the cavity suggested by us is somewhat higher than the values achieved with the other generation methods [2,16] and close to those reported in Refs. [1,4].…”
Section: Resultssupporting
confidence: 86%
“…Researchers are still making considerable efforts to optimize the characteristics of graphene oxide to obtain more flexible pulse output. A number of research groups worldwide have used graphene oxide for passive Q-switching in fiber lasers [50][51][52][53][54][55][56][57][58]. In 2013, Yu et al demonstrated an ytterbium-doped Q-switched fiber laser for the first time [54].…”
Section: Graphene Oxide Based Q-switched Fiber Lasermentioning
confidence: 99%
“…Another configuration of tunable dual-wavelength is demonstrated in [8], wherein a high birefringence FBG stabilizes a dual-wavelength laser produced when the polarization state of each wavelength is altered using a polarization controller. A large number of researchers have investigated the distinctive properties of photonic crystal fibers, such as wide range single mode operation, dispersion flexibility, large mode area and its application in multi-wavelength generation [9][10][11][12]. In most cases, these properties were proven to be wavelength dependent and equivalent to the behavior of wavelength-selective filters [13,14].…”
Section: Introductionmentioning
confidence: 99%